EFFECT OF MODIFICATION OF PEAT SURFACE WITH CHITOSAN ON SORPTION OF COPPER IONS (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The sorption capacities of two peat samples were determined with AAS method. The first one is a natural peat and the second sample is modified with chitosan. The peat was used, was from fields of Vardenis (Gegharkunik Marz of RA). To evaluate the sorption capacity of the sorbents the models of Langmuir and Freundlich were applied. Application of chitosan to the surface of the peat was performed by 3% chitosan solution acidified with citric acid solution. The cross linking was performed by formaldehyde. Sorption processes carried out in static mode.
Keywords: peat, sorbent, copper sorption, Langmuir and Freundlich adsorption models